The lost adventures and team avatar tales ebook - Hicks, Faith Erin (Dark Horse Comics, LLC., 2020)
The comics continuation of Nickelodeon's hit series Avatar: The Last Airbender returns with a treasure trove of short stories, collected for the first time!Follow Team Avatar as they journey through the four nations! From Earth King Kuei to the Kyoshi Warriors, and Mai to the Boulder, your favorite Avatar: The Last Airbender friends are back for a wide-ranging exploration of life in their world. And where they go, danger, fun, and hijinks are sure to follow! This full-color edition collects short stories from The Lost Adventures and Team Avatar Tales, and includes the work of fan-favorite creators like Michael Dante DiMartino, Gene Luen Yang, Gurihiru, Faith Erin Hicks, Kiku Hughes, and many more! Add this gorgeous collection to your bookshelf today! Author: Gene Luen Yang, Faith Erin Hicks. Illustrator: Gurihiru, Sara Goetter.